Teaching, learning, and assessment of science investigation in Year 11: Teachers’ response to NCEA - Moeed, Azra; Hall, Cedric (New Zealand Science Review, 2011)
In New Zealand, the school science curriculum promotes openended science investigation, but the assessment regime in year 11 requires investigation with ‘direction’ and a more limited understanding of investigation. This case study research explored teaching practice and teacher understanding of science investigation, and the connectedness between learning, motivation to learn, and assessment. This paper presents the findings on teacher practice related to the teaching and assessment of science investigation. The results indicate that teacher practice of science investigation changed in response to the internal assessment requirements associated with science investigation for the National Certificate of Educational Achievement (NCEA). The nature of this change raises validity and reliability issues for the assessment of student learning of science investigation.